1998
DOI: 10.1002/(sici)1097-0061(1998100)14:14<1267::aid-yea327>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of expression systems in the yeasts Saccharomyces cerevisiae, Hansenula polymorpha, Klyveromyces lactis, Schizosaccharomyces pombe and Yarrowia lipolytica. cloning of two novel promoters from Yarrowia lipolytica

Abstract: We have compared expression systems based on autonomously replicating vectors in the yeasts Saccharomyces cerevisiae, Schizosaccharomyces pombe, Kluyveromyces lactis, Hansenula polymorpha and Yarrowia lipolytica in order to identify a more suitable host organism for use in the expression cloning method in which S. cerevisiae has traditionally been used. The capacity of the expression systems to secrete active forms of six fungal genes encoding the enzymes galactanase, lipase, polygalacturonase, xylanase and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 0 publications
0
81
0
1
Order By: Relevance
“…heterogenous glycosylation by addition of more than 40 mannose residues to the glycosylation core). In general, the overall length of the mannose chains is lower in H. polymorpha compared to S. cerevisiae and only few cases of hyperglycosylation have been reported in H. polymorpha [50,51]. Hence, H. polymorpha may be a much better candidate to produce human therapeutic proteins compared to S. cerevisiae.…”
Section: Secretionmentioning
confidence: 99%
“…heterogenous glycosylation by addition of more than 40 mannose residues to the glycosylation core). In general, the overall length of the mannose chains is lower in H. polymorpha compared to S. cerevisiae and only few cases of hyperglycosylation have been reported in H. polymorpha [50,51]. Hence, H. polymorpha may be a much better candidate to produce human therapeutic proteins compared to S. cerevisiae.…”
Section: Secretionmentioning
confidence: 99%
“…The most important problem is low ethanol yield and productivity from xylose in wild-type strains, which could be improved by classical selection and metabolic engineering (Kurylenko et al, 2014). It was previously confirmed that this yeast was able to produce high volumetric levels of recombinant endoglucanases derived from other fungi such as A. aculeatus and Humicola insolens (Müller et al 1998). A thermostable endoglucanase was also successfully produced in this yeast (Papendieck et al 2002).…”
Section: Hansenula Polymorphamentioning
confidence: 55%
“…The mono-integrative vector, pINA1313 (Nicaud et al, 2002), was modified by replacing the quasiconstitutive hp4d promoter (Madzak et al, 2000) with the TEF promoter (described by Müller et al, 1998). This replacement still allows high level expression of the cloned EH-encoding gene (driven by the TEF promoter), but with less growth phase dependence, as observed with the hp4d promoter.…”
Section: Construction Of a Constitutive Y Lipolytica Integrative Vecmentioning
confidence: 99%
“…Yarrowia lipolytica has been shown to be one of the most promising yeasts for heterologous protein production (Müller et al, 1998) and has been used for the production of recombinant proteins from a wide variety of organisms (Madzak et al, 2004). The Y. lipolytica system allows for the use of a wide variety of selective markers, promoters and secretion signals and stable site-directed or random integration of either single-or multi-copy expression cassettes into the genome.…”
Section: Introductionmentioning
confidence: 99%